A low-cost business-oriented seaport energy effective management platform - Asimina Dimara; Dimitrios Triantafyllidis; Stelios Krinidis; Nikolaos Ntaras; Olga Koutsogianni; George Tsoukos; Athanasios Giannopoulos; Konstantinos Kitsikoudis; Dimosthenis Ioannidis; Maria Zarkadoula; Apostolos Bizakis; Stavros Antypas; Goumas Georgios; Dimitrios Tzovaras (Institute of Advanced Engineering and Science, 2022)
Many seaports worldwide attempt to gain energy efficiency towards reducing their energy costs while mitigating climate change and environmental effects. In this pa- per, a low-cost business-oriented seaport energy effective management (PERFFECT) platform is introduced. PERFFECT intends to gain knowledge on fundamental port operational and business processes and evaluate them against energy efficiency and environmental footprint. Exploiting all the proposed PERFFECT applications like monitoring, evaluation, forecasting, and optimization, the energy efficiency of the op- erational infrastructure of the port’s is achieved. Port’s energy balance is estimated and used to decide the ports optimal energy usage. Moreover, the traffic volume produced by the gate check is simulated and utilized for further actions. These actions include energy savings and emission reduction recommendations. Finally, the proposed platform is evaluated against real-life data, while the experimental results present the out- come and efficiency of the system. The suggested system results in up to 82.82% light energy savings after a specific suggested action and up to 33% reduction of vehicle emissions, respectively.